2009
DOI: 10.1111/j.1741-4520.2008.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart changes in 17‐day‐old fetuses of diabetic ICR (Institute of Cancer Research) mothers: Improvement with maternal immune stimulation

Abstract: Maternal diabetes mellitus is associated with increased fetal teratogenesis, including cardiovascular defects. Non-specific maternal immune stimulation with Freund's complete adjuvant (FCA) or interferon gamma (IFNgamma) has been associated with protection against birth malformations. Using a diabetic mouse model, late-gestation fetal heart and great vessel morphology were analyzed. Four groups of mice were used: non-diabetic females as a control group, hyperglycemic females induced by streptozotocin as a diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Claudio Gutierrez et al 23 27 found an association between the hyperglycemic environment during pregnancy and the expansion of the ventricular compartment, decreased area of the ventricular myocardium, and dilation of the ascending aorta in the late stages of pregnancy. Other studies point to a correlation between PGD and hypertrophic fetal cardiomyopathy, 17 24 28 29 possibly due to the hyperinsulinemia that the fetus acquires in the context of maternal hyperglycaemia.…”
Section: Maternal Hyperglycemia and Fetal Cardiac Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Claudio Gutierrez et al 23 27 found an association between the hyperglycemic environment during pregnancy and the expansion of the ventricular compartment, decreased area of the ventricular myocardium, and dilation of the ascending aorta in the late stages of pregnancy. Other studies point to a correlation between PGD and hypertrophic fetal cardiomyopathy, 17 24 28 29 possibly due to the hyperinsulinemia that the fetus acquires in the context of maternal hyperglycaemia.…”
Section: Maternal Hyperglycemia and Fetal Cardiac Developmentmentioning
confidence: 99%
“…Hyperglycemia is the main teratogenic factor in diabetic pregnancies, and its presence prior to conception and in the 1 st trimester is associated with an increased risk of disturbed embryonic cardiac development. 7 17 20 21 22 23 24 25 Fetal hyperinsulinemia, inherent in pregnancies of diabetic mothers, is also thought to underlie diabetic embryopathy. 26 …”
Section: Maternal Hyperglycemia and Fetal Cardiac Developmentmentioning
confidence: 99%
See 1 more Smart Citation